ASG2 is a farnesylated DWD protein that acts as ABA negative regulator in Arabidopsis. (8th September 2015) - Dutilleul, Christelle; Ribeiro, Iliana; Blanc, Nathalie; Nezames, Cynthia D.; Deng, Xing Wang; Zglobicki, Piotr; Palacio Barrera, Ana María; Atehortùa, Lucia; Courtois, Martine; Labas, Valérie; Giglioli‐Guivarc'h, Nathalie; Ducos, Eric
Abstract: The tagging‐via‐substrate approach designed for the capture of mammal prenylated proteins was adapted to Arabidopsis cell culture. In this way, proteins are in vivo tagged with an azide‐modified farnesyl moiety and captured thanks to biotin alkyne Click‐iT ® chemistry with further streptavidin‐affinity chromatography. Mass spectrometry analyses identified four small GTPases and ASG2 (ALTERED SEED GERMINATION 2), a protein previously associated to the seed germination gene network. ASG2 is a conserved protein in plants and displays a unique feature that associates WD40 domains and tetratricopeptide repeats. Additionally, we show that ASG2 has a C‐terminal CaaX‐box that is farnesylated in vitro . Protoplast transfections using CaaX prenyltransferase mutants show that farnesylation provokes ASG2 nucleus exclusion. Moreover, ASG2 interacts with DDB1 (DAMAGE DNA BINDING protein 1), and the subcellular localization of this complex depends on ASG2 farnesylation status. Finally, germination and root elongation experiments reveal that asg2 and the farnesyltransferase mutant era1 (ENHANCED RESPONSE TO ABSCISIC ACID (ABA) 1) behave in similar manners when exposed to ABA or salt stress. To our knowledge, ASG2 is the first farnesylated DWD (DDB1 binding WD40) protein related to ABA response in Arabidopsis that may be linked to era1 phenotypes. Abstract : CaaX protein farnesylation is a post‐translational lipidation that targets the Cys of a peculiar C‐terminal motif. Using a tagging‐via‐substrate strategy, we isolated a farnesylated protein in Arabidopsis, ASG2. ASG2 is a DWD (DDB1 interacting WD40) protein that bears a farnesylation‐dependent subcellular localization. Moreover, we show that asg2 mutant mimics era1 (i.e. CaaX protein farnesylation mutant) phenotypes related to seedling development.